Movimentos latino-americanos de trabalhadores uberizados: uma análise desde abaixo - Okusiro, Izabela Ambo (2024)
The present research aimed to analyze the relationship between the social movements of Latin American uberized workers and the possible legislative changes produced in the region. In this sense, it was assumed that, as it is essentially marked by international dependence and the super-exploitation of the workforce, platform capitalism is established with particularities in Latin America. In view of this, the initial hypothesis was that the collective organization of application workers in the region, faced with the regulatory inertia of work on digital platforms, acts in a way to produce legal transformations towards the regulation of their activities, especially because they disproportionately feel the effects of the uberization of work. From the analysis, although the direct relationship between the outbreak of protests and legislative production was not attested, it was possible to confirm the importance of these movements. This is given that, despite having identified the existence of a complex situation, in which several additional factors influence the regulation of the uberization of work, such as political interests, the economic and subjective strength of companies, the dispute of meanings between workers themselves and the clash between the traditional and uberized sectors of the same service, the articulation of workers in these collectives, unions and movements are fundamental for the insertion of regulatory agendas in the legislative scope. With regard to the methodological design, the study was developed following a qualitative methodology, using the deductive method of approach, the descriptive-explanatory objective analysis, and the bibliographic and documentary procedural techniques. Furthermore, its theoretical anchoring was an overlap between Ruy Mauro Marini's Marxist Dependency Theory and the Third World Approaches to International Law (TWAIL) - the latter, focusing, in particular, on Balakrishnan Rajagopal's theory -; furthermore, Beverly Silver's theory served to understand the rise of social movements in the era of platform capitalism.